Entrance and exit effects on oscillatory flow within parallel-plates in standing-wave thermoacoustic system with two different operating frequencies - Mohd Sa'at, Fatimah Al-Zahrah; Allafi, Waleed Almukhtar (King Saud University, 2022)
Thermoacoustics is about conversion between thermal and acoustical energies to provide alternative green technology for power cycle and cooling system. The oscillatory flow across porous structure inside the system is playing the role of energy conversion between the acoustic wave and the surface of the porous structure. Better understanding of fluid dynamics of oscillatory flow inside thermoacoustic system is therefore important for the thermoacoustic based energy conversion system. This paper presents the ‘entrance’ and ‘exit’ effects of the oscillatory flow within a parallel-plate structure that is placed inside a standing-wave thermoacoustic environment. Two-dimensional SST k-ω CFD models which were validated using experimental data and theoretical predictions were used for this investigation. Two different operating frequencies of 14.2 Hz and 23.6 Hz were studied for flow with five different amplitudes that were represented using drive ratios of 0.3%, 0.83%, 1.5%, 2.1% and 3%. These correspond to cases with Reynolds numbers between 5936 and 62926. Due to the cyclic nature of the flow, a region defined as an ‘exit’ region was observed in addition to the usual ‘entrance’ region and the fully developed region for flow inside a channel. The change of shape of velocity profiles from the ‘m’ shape profile, to the ‘slug-like’ profile and ‘parabolic-like’ profile was discussed in relation to the ‘entrance’ and ‘exit’ effects on flow inside the channel. The ‘entrance’ and ‘exit’ effects become bigger as drive ratio increases. The effect of ‘entrance’ and ‘exit’ are slightly reducing as frequency increases from 14.2 Hz to 23.6 Hz. This may be related to the shorter travel distance of fluid as the frequency increases. The results shown in this paper suggest that the flow within a 200 mm parallel-plate structure should be treated as developing flow especially for flow with low resonance frequency at drive ratio higher than 1%.